PENGARUH PERLAKUAN PENCUCIAN DAN PEREBUSAN TERHADAP KADAR RESIDU INSEKTISIDA KLORPIRIFOS DAN KARAKTERISTIK KACANG PANJANG (Vigna sinensis) - Putri Dinanti, Made Rizki; Lani Triani, I Gusti Ayu; Satriawan, I Ketut (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 3 No 2 (2015): Juni)
The research aims were to determine the influence of washing and boiling time on the chlorpyrifos residue levels of the long beans, to determine the level of preference for long beans after washing and boiling treatment, and to determine the best washing and boiling time to reduce chlorpyrifos insecticide residue and with favorite characteristics long beans result. This research used randomized block design with factorial pattern. The first factor (washing time) consisted of 3 level namely without washing, 10 and 20 seconds process time, and the second factor (boiling time) consisted of 3 level namely without boiling, 5 and 10 minutes process time. Each treatment grouped into 3 groups based on the time implementation. Samples tested objectively and evaluation sensory to determine the best treatment. The results residue showed that washing and boiling time effect on the levels of insecticides chlorpyrifos and characteristic of long beans. Sensory evaluation preference on taste and overall acceptance in the long bean, washing treatment 20 seconds with boiling 10 minutes, resulting in long bean with flavor favorite and overall acceptance rather preferred. The 20 seconds washing time with boiling 10 minutes was the right treatment to produce a drop in levels of the chlorpyrifos residues, amounting 0.0022 mg/kg and characteristics preferred by the value of the flavor 6.25 (like), the texture of 4.60 (soft), the color of 4.10 (green bit old), and a 5.30 overall acceptance (rather like)
Keywords: 42,